1993
DOI: 10.1111/j.1095-8312.1993.tb00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological correlates of chiasma frequency and recombination index of plants

Abstract: This paper tests four theories of the maintenance of genetic recombination using published chiasma frequencies of 194 plant species representing 15 families of angiosperms. The theories are that recombination is favoured by environmental unpredictability, by fluctuating selection, by mutational load or by sib-competition. The level of genetic recombination was approximated by recombination index and by the number of excess chiasmata. Both measures were higher in animaldispersed than in other species and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 59 publications
(11 reference statements)
0
12
2
Order By: Relevance
“…Dasmaceno Junior et al (2010) reported similar RI values to those found in this study for C. papaya and V. monoecious (26.0 and 25.8 respectively). These values can be considered satisfactory, based on a review of the RI of 194 species of 46 genera and 15 angiosperm families, with values ranging from 6.56 to 75.2, with a mean of 26.9 (Koella 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Dasmaceno Junior et al (2010) reported similar RI values to those found in this study for C. papaya and V. monoecious (26.0 and 25.8 respectively). These values can be considered satisfactory, based on a review of the RI of 194 species of 46 genera and 15 angiosperm families, with values ranging from 6.56 to 75.2, with a mean of 26.9 (Koella 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Finding a pattern consistent with this general population genetic prediction is, of course, not firm evidence that male-female dimorphism in haploid selection is the evolutionary force generating heterochiasmy. Other correlates of selfing rates might have to be closely examined [23]. However, we consider this explanation the most parsimonious so far.…”
Section: Resultsmentioning
confidence: 99%
“…However, particular issues related to the selective or stochastic forces that shape independently each particular species might tend to blur these predictions. Indeed, different ecological and selective patterns might result in altered levels of recombination [6-8]. For example, domesticated plants tend to have higher rates of recombination than their wild ancestors or relatives [7].…”
Section: Discussionmentioning
confidence: 99%